FC 122: Effects of Canagliflozin on Cardiovascular and Kidney Events in Patients With Chronic Kidney Disease With and Without Peripheral Vascular Disease: Integrated Analysis From the Canvas Program and Credence Trial. (3rd May 2022) - Levin, Adeera; Poirier, Paul; Seufert, Jochen; Slee, April; Rapattoni, Wally; Ang, Fernando; Wheeler, David
Abstract: BACKGROUND AND AIMS: Type 2 diabetes mellitus (T2DM) is associated with comorbidities, such as chronic kidney disease (CKD) and peripheral vascular disease (PVD), which may increase risk of cardiovascular (CV) and kidney events. Canagliflozin, a sodium glucose co-transporter 2 (SGLT2) inhibitor, reduced the risk of CV and kidney events in patients with T2DM and high CV risk or nephropathy in the CANVAS Program and CREDENCE trial, respectively. The effects of canagliflozin on CV and kidney outcomes in patients with CKD with and without PVD remain unknown. METHOD: This post hoc analysis included integrated, pooled data from the CANVAS Program and the CREDENCE trial. The effects of canagliflozin compared with placebo on CV and kidney outcomes were assessed in patients with CKD with and without PVD at baseline. CKD was defined as estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 and PVD was defined based on investigator classification on the electronic case report form without requirement for specific clinical evaluation or imaging. Propensity score (PS) matching was used to balance patient demographics and baseline clinical characteristics between groups. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were estimated using Cox regression models. RESULTS: A total of 14 543 participants from the CANVAS Program ( N  = 10 142) and CREDENCE ( N  = 4401) were included. Of these, 3514 had CKD alone (canagliflozin, n  = 1792; placebo, n  = 1722; mean eGFR, 46 mL/min/1.73 m 2 ; symptomatic CV disease history, 49%; insulin use, 64%) and 1156 had CKD + PVD (canagliflozin, n  = 626; placebo, n  = 530; mean eGFR, 46 mL/min/1.73 m 2 ; symptomatic CV disease history, 96%; insulin use, 74%) at baseline. Canagliflozin was associated with a reduced risk of major adverse cardiovascular events (MACE), the composite of hospitalization for heart failure (HHF) or CV death (HHF/CV death), doubling of serum creatinine (dSCr), end-stage kidney disease (ESKD) and the composite of ESKD or dSCr compared with placebo in patients with CKD with and without PVD (Figure 1 A). After matching, 3210 patients had CKD alone (mean eGFR, 46 mL/min/1.73 m 2 ; symptomatic CV disease history, 49%; insulin use, 64%) and 966 had CKD + PVD (mean eGFR, 46 mL/min/1.73 m 2 ; symptomatic CV disease history, 98%; insulin use, 74%), with equal numbers in the canagliflozin and placebo groups. In the PS-matched groups, canagliflozin was associated with a reduced risk of MACE, HHF/CV death, dSCr, ESKD and the composite of ESKD or dSCr compared with placebo in patients with CKD with and without PVD (Figure 1 B). CONCLUSION: Canagliflozin significantly reduced the risk of MACE, HHF/CV death, dSCr, ESKD, and the composite of ESKD or dSCr in patients with CKD with and without PVD, suggesting that the beneficial effects of canagliflozin on CV and kidney outcomes are consistent and can be seen in patients regardless of these comorbidities.